Digital literacy and Web curriculum in teacher training during the COVID-19 pandemic: an experience report at the Educational Technology Center in the interior of the Acre Amazon - de Magalhães Melo, Francisca; Cruz, Maria Aurinete Silva da; Silva-Antunes, Paula Tatiana da (The ESPecialist, 2024)
This article seeks to discuss the benefits and challenges faced during teacher training during the Covid-19 pandemic. As a theoretical path, it weaves discussions around Web curriculum, teacher training and digital literacy. The methodology is qualitative-interpretative in nature (Bortoni-Ricardo, 2008; Paiva, 2019), and uses the experience reports of educational trainers and materials prepared for workshops as analysis data. The results showed a greater understanding of digital technologies for education, however, it is necessary to face the problems of infrastructure, access and teacher training